Výrobní proces součásti ze základny přístroje - Kunst, Ondřej (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2021)
Bakalářská práce se věnuje řešení výrobního procesu součásti ze základny přístroje. Úvodní kapitola se zabývá rozborem výrobku a podrobným popisem softwarové konstrukce 3D modelu. Další dvě části jsou věnovány volbě strojů, nástrojů a měřidel. Na ně navazuje kapitola s rozborem technologií ve výrobním postupu. V předposlední kapitole jsou popsány konkrétní NC programy pro výrobu na CNC stroji. Závěrečná kapitola je věnována orientačnímu výrobnímu výpočtu.

The bachelor's thesis focuses on the solution of the production process of a part from the apparatus base. Introduction of the thesis deals with the analysis of the product and a detailed description of the software construction of the 3D model. The next two parts are devoted to the choice of machines, instruments and gauges. This is followed by a chapter with the analysis of technologies used in the production procedures. The penultimate chapter describes the specific NC programs for the production on the CNC machinery. The final chapter is devoted to the indicative calculation of production process.
Production process of a part from the base of a device
Keywords: frézování; výrobní postup; NC program; CNC stroje; milling; manufacturing process; NC program; CNC machinery